2016
DOI: 10.1155/2016/2968106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Key Genes and Pathways in Esophageal Carcinoma

Abstract: Objective. Esophageal carcinoma (EC) is a frequently common malignancy of gastrointestinal cancer in the world. This study aims to screen key genes and pathways in EC and elucidate the mechanism of it. Methods. 5 microarray datasets of EC were downloaded from Gene Expression Omnibus. Differentially expressed genes (DEGs) were screened by bioinformatics analysis. Gene Ontology (GO) enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and protein-protein interaction (PPI) network construction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…CDK4 was the node with the highest degree of interaction and was the most connected hub protein, interacting with 30 genes in the regulatory network. This result was consistent with that by Su et al ( 41 ), which also indicated that CDK4 was the most significantly upregulated gene by analyzing 5 mRNA expression datasets of EC tissues/cell lines from GEO. A recent study revealed that CDK4 had a negative association with EC-related gene 4, which has a tumor suppressor function in ESCC ( 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…CDK4 was the node with the highest degree of interaction and was the most connected hub protein, interacting with 30 genes in the regulatory network. This result was consistent with that by Su et al ( 41 ), which also indicated that CDK4 was the most significantly upregulated gene by analyzing 5 mRNA expression datasets of EC tissues/cell lines from GEO. A recent study revealed that CDK4 had a negative association with EC-related gene 4, which has a tumor suppressor function in ESCC ( 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study has identified key DEGs in ESCC by integrated analysis of five microarray datasets from GEO (19). With GEO database updated, we identified DEGs in ESCC by integrated analysis of ten microarray datasets with larger sample size in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical data showed that overexpression of CDKN3 indicated poor cancer prognosis13, 16. It had been documented that CDKN3 is upregulated in esophageal cancer17, but advanced research on the detailed biological function is still absent.…”
Section: Introductionmentioning
confidence: 99%